2008
DOI: 10.1523/jneurosci.2684-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous High-Frequency (10–80 Hz) Oscillations during Up States in the Cerebral CortexIn Vitro

Abstract: High-frequency oscillations in cortical networks have been linked to a variety of cognitive and perceptual processes. They have also been recorded in small cortical slices in vitro, indicating that neuronal synchronization at these frequencies is generated in the local cortical circuit. However, in vitro experiments have hitherto necessitated exogenous pharmacological or electrical stimulation to generate robust synchronized activity in the ␤/␥ range. Here, we demonstrate that the isolated cortical microcircui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
115
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 75 publications
14
115
1
Order By: Relevance
“…In vitro studies have also demonstrated that fast oscillations in the gamma range occur spontaneously in isolated cortical networks during up-down states usually associated to both sleep and anesthesia (Sanchez-Vives et al, 2000;Dickson et al, 2003). Also, under these experimental conditions -which more closely represent a physiological synchronization that is independent from pharmacological manipulations -both interneurons and principal cells contribute to fast oscillation generation (Dickson et al, 2003;Gnatkovsky et al, 2007;Compte et al, 2008). As further discussed in Section 6, fast activities at 20-80 Hz can also be observed in association with prolonged periods of epileptiform synchroniations that resemble electrographic seizures, and are induced by experimental procedures that do not block GABA A receptor-mediated signaling Köhling et al, 2000;Fujiwara-Tsukamoto et al, 2004;Gnatkowsky et al, 2008).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%
“…In vitro studies have also demonstrated that fast oscillations in the gamma range occur spontaneously in isolated cortical networks during up-down states usually associated to both sleep and anesthesia (Sanchez-Vives et al, 2000;Dickson et al, 2003). Also, under these experimental conditions -which more closely represent a physiological synchronization that is independent from pharmacological manipulations -both interneurons and principal cells contribute to fast oscillation generation (Dickson et al, 2003;Gnatkovsky et al, 2007;Compte et al, 2008). As further discussed in Section 6, fast activities at 20-80 Hz can also be observed in association with prolonged periods of epileptiform synchroniations that resemble electrographic seizures, and are induced by experimental procedures that do not block GABA A receptor-mediated signaling Köhling et al, 2000;Fujiwara-Tsukamoto et al, 2004;Gnatkowsky et al, 2008).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%
“…In particular, gamma oscillations (40 -120 Hz), usually associated with waking functions such as sensory binding (Singer and Gray, 1995), attention (Fries et al, 2001), encoding and retrieval of memory traces (Montgomery and Buzsáki, 2007), are also present during slow-wave sleep (SWS). In vivo (Steriade et al, 1996;Grenier et al, 2001;Isomura et al, 2006;Mukovski et al, 2007;Mena-Segovia et al, 2008) and in vitro (Dickson et al, 2003;Compte et al, 2008) recordings in the neocortex indicate that gamma oscillations occur during "UP" states, i.e., rhythmic cycles of suprathreshold membrane potential depolarizations occurring synchronously in large neuronal populations and reflected on electroencephalography (EEG) recordings as largeamplitude slow waves (Steriade et al, 1993). Network dynamics during UP states have been proposed to be equivalent to those observed during the waking state (Destexhe et al, 2007;Luczak et al, 2007;Haider and McCormick, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of reactivation to memory is clear from these systems-level studies. Circuit reactivation in slice is remarkably similar to activity in vivo during SWA 25,26 and provides a useful tool to examine synaptic plasticity in this context 13 . We find that circuit reactivations in vitro display stereotyped spatiotemporal patterns of neuronal activity consistent with observations of replay in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…1a,b,c). Thus, the UP state is the neuronal substrate for circuit activity [15][16][17]25,26 . We refer to the recurrence of these distinct spontaneous events as circuit reactivations.…”
Section: Resultsmentioning
confidence: 99%